Convergent evolution increases boron transport through SNPs and tandem duplications at BOR1 and BOR2 in Arabidopsis thaliana - Emmanuel Tergemina; Célia Neto; Md Mamunur Rashid; Herculano Dinis; David E. Salt; Angela M. Hancock (Proceedings of the National Academy of Sciences, 2026)
Boron (B) is a crucial micronutrient, particularly in volcanic soils where its deficiency hampers agriculture. Here, we investigate the genetic basis of leaf B accumulation in natural populations of Arabidopsis thaliana that colonized volcanic islands in Cape Verde. Using a combination of genome-wide association studies (GWAS) and mapping in a recombinant intercross population, we identified a case of convergent phenotypic evolution in which multiple variants in the two principal B transporter genes, BOR1 and BOR2 , increase leaf B accumulation in parallel. These include multiple tandem duplications at BOR1 that arose independently in different populations. Overall, this study reveals a remarkable case of convergent evolution occurring within a relatively short time scale, where different types of de novo mutations at B efflux transporter genes achieve similar phenotypic outcomes. Further, our findings show that integrating recombinant populations with GWAS in natural populations can improve power to overcome allelic heterogeneity.